2023
DOI: 10.1371/journal.pone.0281304
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative upper tract invasive diagnostic modalities are associated with intravesical recurrence following surgery for upper tract urothelial carcinoma: A population-based study

Abstract: Background Intravesical recurrence (IVR) after surgery for upper tract urothelial carcinoma (UTUC) is a clinical problem. We investigated if preoperative invasive diagnostic modalities (IDM) such as antegrade/retrograde uretero-pyelography and/or selective urine cytology/barbotage, and URS with or without concomitant biopsy are associated with IVR after radical surgery for UTUC. Risk of death from urothelial cancer and all causes was investigated as secondary outcomes. Methods We investigated a population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Although invasive diagnostic modalities independently have been associated with IVR in population-based series [9] such association could not be confirmed in the current data even after additional analyses with preoperative instrumentation of the upper urinary tract included as exposure. The lack of information about other known risk factors for IVR such as tumour size, hydronephrosis and tumour multiplicity when performing time-to-event analysis [10] together with limited statistical power in the present study are possible explanations for the lack of association with IVRFS in the current study.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Although invasive diagnostic modalities independently have been associated with IVR in population-based series [9] such association could not be confirmed in the current data even after additional analyses with preoperative instrumentation of the upper urinary tract included as exposure. The lack of information about other known risk factors for IVR such as tumour size, hydronephrosis and tumour multiplicity when performing time-to-event analysis [10] together with limited statistical power in the present study are possible explanations for the lack of association with IVRFS in the current study.…”
Section: Discussioncontrasting
confidence: 72%
“…The rare and heterogenous nature of UTUC constitutes a challenge for the urologist both in planning the diagnostic work-up and in surgical treatment. To improve survival outcomes in patients undergoing RNU, quality of care indicators including a complete removal of the distal ureter with excision of a bladder cuff has been proposed as one of five measures to achieve pentafecta at RNU [14] Despite recommendations in guidelines, proportions without bladder cuff excision up to 30% in patients operated with RNU have been published [9,15] In comparison, in the present study, 15% (22/150) of the patients were operated without bladder cuff excision. However, during later years in the authors' institution, patients subjected to SVs tended to decrease, which might be partly due to increased surgical volumes over time [16].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Diagnostic URS without biopsy was not associated with worse IVRFS [7]. Table 1 summarizes the studies assessing the association between URS, IVR (intravesical recurrence), and RFS (recurrence-free survival) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A study on 143 patients demonstrated a pathological phenotype-specific association between pre-operation URS and oncological outcomes, as the subgroup of patients with non-papillary and ≥pT3 UTUC had poorer overall and progression-free survival [23].…”
Section: Ureterorenoscopy and Biopsymentioning
confidence: 99%